Metastatic inhibitory effect of gallic acid combined with cisplatin on hela cells proliferation - Zamberi, Nurul Nadia Mohamad (2020)
Due to the multiple adverse effects of chemotherapy treatment, more researches with natural product discovery has been conducted to treat various types of cancer. A polyphenol derivative, gallic acid, was previously reported to combat the growth of cancer cells. Hence, this study aims to assess the metastatic inhibitory effect of gallic acid combined with cisplatin against HeLa cells. Cell migration, cell invasion and cell proliferation were measured by scratch-wound healing assay, Transwell invasion assay and colony formation assay, respectively. After 24-hour of scratch-wound healing assay, the combined treatment showed significant decrease in wound closure rate where 43.08 ± 6.21% of the wound was filled by the HeLa cells in comparison to control wound width. Combination of gallic acid and cisplatin also exerted a significant decrease in the number of invaded cells at 44.55 ± 6.04% as compared to the control group by Transwell invasion assay. Gallic acid and cisplatin were able to significantly reduce the proliferation HeLa cells by colony formation assay. However, the effect that was produced by their combination was greater than that of each agent alone. Hence further study either in vitro and in vivo is required to strengthen the current findings such as research regarding the involvement of PI3K/AKT/mTOR signaling pathway in decreasing migration and invasion capability of HeLa cells.